Automatização da geração de casos de testes: um estudo de caso na empresa Exactus Software - Neves, Romulo de Almeida (2019)
Context: Model Driven Development (MDD) raises the importance of models within the of the software, incorporating them as an part of the final product by means of modeling techniques and code generation. With this, part of the software complexity is hidden inside the code generators. In addition the software is composed of graphical interfaces called User Interfaces (UIs), that are responsible for performing the interaction of the software with the user, thus offering greater flexibility in the execution of tasks. This interface is formed by widgets that allow the use of software such as buttons, menu items, and text boxes. Problem: The tests are performed manually, thereby the cost associated with the development of test cases is high. Objective: The main objective of this work is to check the efficiency of approaches to the generation of test cases from models in the development process in industry. Justification: Ensure software quality, reduce overall software lifecycle time, and costs associated with the tests. Method: Develop and elaborate test case generation techniques within different contexts and evaluate its effectiveness for software development processes. Two case studies were conducted: one for the generation of test cases using Model-Driven Testing within a process based on Model-Driven Development; and one for generating test cases using interface components in Web applications. Results: Each of the approaches was validated separately and the results indicate evidence that: (i) the generation of cases the Exactus Software MDD process automation improves the efficiency of test approach at Exactus Software; and (ii) the Morpheus Web Testing approach can achieve greater coverage of code compared to thecnical of the art state, because for all the scenarios Morpheus Web Testing was able to achieve a better performance on average. Conclusions: In both case studies the coverage values reached represent evidence that the results obtained from the proposed approaches contribute to the process of Engineering automated testing software in the industry. Considering the second case study, specifically, the proposed technique, including results superior to a state-of-the-art technique (Crawljax). Besides that, the approaches also presented the follows contributions: automation of the industry; and with the automation process of the tests an improvement in the quality is expected the software and a reduction in development costs.